Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region. (February 2023) - Jordan, Benjamin S.; Readle, Jason D.; Cooper, Jeffrey R.; Cook, Matthew; Hayward, Jason P.; Daniel Hartman, J.; Forrest, Dean; Hall, Howard L.
Abstract: Most modern uranium enrichers use centrifuges to separate 235 U [Uranium 235] and 238 U [Uranium 238] in the gaseous form, UF6 [uranium hexafluoride]. Monitoring the enrichment level of the material being produced in a Gaseous Centrifuge Enrichment Plant (GCEP) or in a single centrifuge is important to the commercial enricher as well as those tasked with monitoring the enrichment activities of declared facilities, such as the International Atomic Energy Agency (IAEA). Here, methods for determining UF6 assay using a femtosecond laser-induced plasma are reported. These techniques resulted in assay measurements within 0.28% of the actual 235 U content with a standard deviation of 0.90%, demonstrating the potential effectiveness and applicability of using femtosecond lasers in actual enrichment plants to measure UF6 assay through Laser-Induced Plasma Emission Spectroscopy (LIBS).